2020
DOI: 10.3389/fonc.2020.552283
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products Acts as a Fuel to Colorectal Cancer Development

Abstract: Receptor for advanced glycation end-products (RAGE) is a multiligand binding and single-pass transmembrane protein taken in diverse chronic inflammatory conditions. RAGE behaves as a pattern recognition receptor, which binds and is engaged in the cellular response to a variety of damage-associated molecular pattern molecules, as well as HMGB1, S100 proteins, and AGEs (advanced glycation end-products). The RAGE activation turns out to a formation of numerous intracellular signaling mechanisms, resulting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 208 publications
(277 reference statements)
4
48
0
Order By: Relevance
“…15 To date, there are already several literature overviews supporting a direct link between α-dC -AGE/AGE-proteins and the activation of RAGE 16,17 as well as a recent review on colorectal cancer describing the involvement of AGEs and their precursors (α-dC) and, especially, RAGE in cancer progression. 57 RAGE, a multiligand cell surface receptor, has been reported to correlate with the poor therapeutic outcomes and malignancy of HCC as comprehensively reviewed by Takino et al 58 Moreover, in the same study, the researchers underlined that interactions between toxic AGEs and RAGE-induced oxidative stress, which may in turn lead to adverse effects in tumor cells and HSC during liver disease progression. 58 In their study, Li and colleagues confirmed RAGE overexpression in HCC and its important role in cancerous disease progression, associated with proliferation and resistance to sorafenib.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 To date, there are already several literature overviews supporting a direct link between α-dC -AGE/AGE-proteins and the activation of RAGE 16,17 as well as a recent review on colorectal cancer describing the involvement of AGEs and their precursors (α-dC) and, especially, RAGE in cancer progression. 57 RAGE, a multiligand cell surface receptor, has been reported to correlate with the poor therapeutic outcomes and malignancy of HCC as comprehensively reviewed by Takino et al 58 Moreover, in the same study, the researchers underlined that interactions between toxic AGEs and RAGE-induced oxidative stress, which may in turn lead to adverse effects in tumor cells and HSC during liver disease progression. 58 In their study, Li and colleagues confirmed RAGE overexpression in HCC and its important role in cancerous disease progression, associated with proliferation and resistance to sorafenib.…”
Section: Discussionmentioning
confidence: 98%
“… 15 To date, there are already several literature overviews supporting a direct link between α-dC – AGE/AGE-proteins and the activation of RAGE 16 , 17 as well as a recent review on colorectal cancer describing the involvement of AGEs and their precursors (α-dC) and, especially, RAGE in cancer progression. 57 …”
Section: Discussionmentioning
confidence: 99%
“…Both HMGB1 and AGE bind to RAGE [ 12 ]. We have previously reported the differences between HMGB1 and AGE as RAGE ligands [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a cell membrane receptor that has the ability to bind to multiple ligands, such as AGE, HMGB1, and S100B [ 11 ]. HMGB1 enhances oxidative stress by binding to RAGE via multiple pathways, such as mitogen-activated protein kinase, p21ras, nuclear factor (NF)-κB, AKT, phosphoinositide 3-kinase, and Wnt [ 12 ]. Importantly, RAGE also binds to AGE [ 13 , 14 ], which is generated at high levels in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…RAGE expression is upregulated in a vast majority of cancers, but its expression is very low under physiological conditions. Specific examples of types of cancer in which RAGE expression is upregulated include colorectal cancer ( 32 ), pancreatic cancer ( 33 ), prostate cancer ( 34 ), lung cancer ( 35 ) and breast cancer, and in breast cancer, it has been reported that the RAGE rs1800624 polymorphism may increase the risk of breast cancer ( 36 ).…”
Section: Tages In Cancermentioning
confidence: 99%